Anthropocentric and theocentric spirituality as an object of psychological research - Jaworski Romuald (Journal for Perspectives of Economic Political and Social Integration, 2015)
The characteristic direction of psychological and theological interpretations of spirituality is very important. The traditional psychological approach to the spiritual sphere is characterised by reductionism, which consists in reducing spiritual experiences to mental experiences, or even biological processes. The studies in the field of religion psychology led to distinguish between two types of spirituality. The first one is theocentric spirituality, where human being places God in the centre of his interest and life in general. The second type of spirituality is anthropocentric spirituality, focused on human being, his own aspirations, preferences and needs. Both types of spirituality have certain value. Their close characteristics includes sources of inspiration, purpose, presented image of God, as well as understanding of spirituality and manner of realizing spiritual life. In order to distinguish between two types of spirituality, anthropocentric and theocentric, in practice, a proper research method – Range of Theocentric and Anthropocentric Spirituality (SDT – DA) had to be developed. The individuals with theocentric spirituality displayed a higher level of stability and emotional balance, better social adjustment, higher sense of duty and attachment to acceptable social standards, deeper and more satisfactory contacts with other human beings, more trust and openness towards others, as well as higher trust to themselves and to God. Such individuals are better at handling difficulties and have optimistic attitude to life.